2020
DOI: 10.1016/j.japh.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes about community pharmacy access to HIV prevention medications in California

Abstract: Increasing access to human immunodeficiency virus (HIV) pre-exposure prophylaxis (PrEP) and postexposure prophylaxis (PEP) is a high priority for the Ending the HIV Epidemic Initiative. Expanding access to PrEP and PEP through a variety of health care settings, including community pharmacies, may increase access in communities most in need. California is the first state to allow community pharmacists to furnish PrEP and PEP directly to consumers. Our objective was to assess attitudes among key stakeholders abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 25 publications
1
51
0
1
Order By: Relevance
“…Twenty-four empirical studies concerning pharmacist and patient perceptions of PrEP were identified (Table 1 ). The sample size of such studies ranged from 9 [ 44 ] to 7148 [ 45 ]. Fourteen studies contained primary observational data concerning practicing pharmacists’ and Doctor of Pharmacy (PharmD) students’ knowledge, perceptions, and attitudes of pharmacy-based PrEP interventions [ 44 , 46 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-four empirical studies concerning pharmacist and patient perceptions of PrEP were identified (Table 1 ). The sample size of such studies ranged from 9 [ 44 ] to 7148 [ 45 ]. Fourteen studies contained primary observational data concerning practicing pharmacists’ and Doctor of Pharmacy (PharmD) students’ knowledge, perceptions, and attitudes of pharmacy-based PrEP interventions [ 44 , 46 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The sample size of such studies ranged from 9 [ 44 ] to 7148 [ 45 ]. Fourteen studies contained primary observational data concerning practicing pharmacists’ and Doctor of Pharmacy (PharmD) students’ knowledge, perceptions, and attitudes of pharmacy-based PrEP interventions [ 44 , 46 55 ]. Pharmacists and/or pharmacy students from all four of the U.S. Census Bureau regions were represented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In a qualitative case study assessing the attitudes of key pharmacy stakeholders toward PrEP and PEP furnishing, most agreed that community pharmacists are widely accessible providers, that PrEP and PEP furnishing protocols are similar to those for other preventive medications, and that policies that allow pharmacists to furnish could increase access. 15 Similarly, in a study assessing patient perspectives of PrEP furnishing, 100% of patients agreed or strongly agreed that having pharmacistprescribed PrEP would benefit their community, and 93.3% of patients agreed or strongly agreed they would feel comfortable seeking PrEP information or HIV testing from a pharmacist. 16 Previous research has found that pharmacist furnishing can increase access to other therapies, including hormonal contraception, naloxone, smoking cessation medications, vaccines, and syringes.…”
mentioning
confidence: 99%
“…[17][18][19][20][21] Before 2019, pharmacists in California could furnish PrEP and PEP under a formal collaborative practice agreement (CPA) in which a medical provider and a pharmacist form a partnership. 15 Although this method is difficult to implement, it led community pharmacies to provide and expand access to PrEP/PEP. 22 As of 2020, PrEP and PEP services had been implemented in some community pharmacies and ambulatory care clinics.…”
mentioning
confidence: 99%